The Tradition of Fire War as Self-Purification in the Nyepi Ritual Among the Hindu Community in Mataram City - Zalfa Zila (Tabéq Care Center and UIN Mataram, 2025)
This study aims to determine the meaning of the Fire War tradition as a form of self-purification in the Nyepi ritual among the Hindu community in Mataram City. The Fire War tradition, held since 1819, is a symbolic ritual to ward off evil, remove negative energy, and purify oneself before Nyepi Day. The focus of this study includes: (1) how the Fire War tradition is carried out as a form of self-purification in the Nyepi ritual among the Hindu community in Mataram City, and (2) the meaning of the Fire War tradition as a form of self-purification in the Nyepi ritual among the Hindu community in Mataram City. This study uses a descriptive qualitative method with Victor Turner’s liminality theory as the basis for analysis, which includes three stages: separation, liminality, and reintegration. The results show that the Fire War tradition has a deep spiritual meaning, serving to purify oneself of bad traits and negative energy while also strengthening social solidarity among Hindus. In this tradition, fire symbolises spiritual cleansing and renewal, allowing Hindus to welcome Nyepi with a clean, calm soul. In addition to its religious value, this tradition also plays an important role in strengthening togetherness, reinforcing Hindu cultural identity, and preserving local wisdom amid the tide of modernisation.